Upaya Meningkatkan Kompetensi Guru dalam Menyusun RPP melalui Supervisi Akademik di Sekolah Binaan SDN 90/X Mendahara Ilir pada Semester Genap Tahun ajaran 2021/2022 - Amir Amir (Journal on Education, 2023)
This study aims to obtain information and discuss efforts to improve teacher competency in preparing lesson plans through academic supervision at SDN 90/X Mendahara Ilir target schools in the even semester of the 2021/2022 academic year. This research is a school action research. This research was conducted at SDN 90/X Mendahara Ilir in the even semester of the 2021/2022 academic year with 7 teachers as subjects. Data was collected through observation sheets, field notes, and documentation. Data analysis techniques use percentages and data reduction. Based on the results of the study, it can be concluded that through academic supervision, teachers can improve competence in preparing lesson plans at SDN 90/X Mendahara Ilir target schools by giving rewards and marked by an increase in each cycle.